Treatment strategies for rapid recurrence and progression after surgery for stage I pulmonary pleomorphic carcinoma: a case report and literature review - Zhang, Jing; Xiong, Wenji; Wang, Hong; Sun, Lemeng; Chen, Chen; Sun, Xueru; Man, Xiuyue; Yang, Lei; Li, Zhihong (Frontiers in Immunology, 2025)
Pulmonary pleomorphic carcinoma (PPC) is a rare and poorly differentiated subtype of non-small cell lung cancer (NSCLC), primarily originating from non-epithelial tissue. Currently, there is no consensus on optimal treatment strategies for patients with PPC presenting diverse clinical features. This report describes an elderly male with stage I pulmonary pleomorphic carcinoma. Five months after surgery, the disease progressed rapidly, resulting in vertebral metastasis. Following a second surgery, the patient was treated with a programmed cell death protein-1 (PD-1) inhibitor combined with cytotoxic therapy. This regimen led to significant tumor shrinkage, achieving a partial response (PR). These findings suggest that combining immune checkpoint inhibitors (ICIs) with chemotherapy may improve outcomes for patients with advanced PPC.